Tank‐Circuit Assisted Coupling Method for Sympathetic Laser Cooling. Issue 7 (7th May 2021) - Tu, Bingsheng; Hahne, Felix; Arapoglou, Ioanna; Egl, Alexander; Heiße, Fabian; Höcker, Martin; König, Charlotte; Morgner, Jonathan; Sailer, Tim; Weigel, Andreas; Wolf, Robert; Sturm, Sven
Abstract: The coupling of the motion of two ion species in separate Penning traps via a common tank circuit is discussed. The enhancement of the coupling assisted by the tank circuit is demonstrated by an avoided crossing behavior measurement of the motional modes of two coupled ions. An intermittent laser cooling method for sympathetic cooling is proposed and a theoretical description is provided. The technique enables tuning of the coupling strength between two ion species in separate traps and thus allows for efficient sympathetic cooling of an arbitrary type of single ion for high‐precision Penning‐trap experiments. Abstract : A novel scheme is presented that allows to efficiently cool arbitrary ions by coupling them to a directly laser cooled ion in a separate Penning trap. The results demonstrate how a common tank circuit can drastically enhance the coupling, resulting in the expected avoided‐crossing behavior. This technique holds promise to enable millikelvin cooling of arbitrary ions in Penning traps.